The Influence of Targeting Strategies on Purchasing Decisions at Maros Homemade Eating Stalls - Hermawaty Remba Kasim; Hasriani Hasriani; Mahyus Mahyus (Newinera Publisher, 2020)
The research aims to find out influence of targeting strategies on purchasing decisions at Maros Homemade food stalls in Maros Regency. This type of research is descriptive-quantitative research with data analysis techniques using exact science using observation, questionnaires, and documentation with data analysis techniques using multiple linear regression analysis. The results showed that: Partially targeting has a significant effect on purchasing decisions, with t count = 6.954> t table = 2.009 and a significance value of 0.000. This targeting strategy can be done by increasing the right marketing strategy and selecting targets in accordance with the target at the food stalls so that consumers are interested in making purchasing decisions.